Diversité des tiques de bovins et variation saisonnière des infestations dans la région maritime au Togo - Mollong, E.; Nuto, Y.; Rabiétou, C.; Amevoin, K. (Tropicultura, 2018)
Diversity of Cattle Ticks and Seasonal Variation of Infestations in the Maritime Region of Togo. Ticks are a major constraint for the development of livestock production in West Africa, particularly in Togo. With a view to reducing the level of tick infestation below economic thresholds of harm, the diversity and parasite load of these pests was assessed by collecting them from July 2013 to June 2014 in 9 localities in the Maritime Region in Togo. A total of 18,378 adult ticks were collected from cattle. These ticks belong to 5 genera and 17 species of which the most abundant and frequent are: Amblyomma variegatum (Fabricius, 1794) (38.30%), Rhipicephalus (Boophilus) microplus (31.84%), Rhipicephalus (Boophilus) decoloratus (17.43%). The different localities surveyed were similar in terms of specific diversity of ticks. The level of infestation of cattle by the 3 most abundant tick species was higher in Kamina with a mean of 22.02 ± 15.88 ticks/bovine/month (F = 5.836; df = 107; P<0.000). These results are core data for the identification of parasitic pests associated with bovine ticks and the assessment of the economic importance of bovine ticks in Togo.